Perokok Aktif Di Bawah Umur Dalam Perspektif Peraturan Pemerintah Republik Indonesia Nomor 109 Tahun 2012 Dan Keterkaitannya Dengan Norma Kesopanan Di Lingkungan Keluarga, Sekolah, Dan Masyarakat (Analisis Isi Dalam Film Sex, Lies, And Cigarettes) - Dian Permatahati, Rieska; , Drs. Yulianto Bambang Setyadi, M.Si (2016)
This study aimed to describe the active under age smokers in the film Sex, Lies, and Cigarettes to describe the use of the film Sex, Lies, and Cigarettes as a learning medium PPKn in applying the norms of decency in a family environment, school, and community. This type of research is qualitative descriptive. This research subject is the film Sex, Lies, and Cigarettes. The object of research is active underage smokers. Data collection techniques in this study using the method of documentation and literature study. Test the validity of the data by triangulation of data sources and triangulation techniques or methods of data collection. The data analysis applying interactive models through data collection, data reduction, and conclusion. The results of this study can be concluded the film Sex, Lies, and Cigarettes can be used as a medium of Pancasila and Citizenship Education Learning, to convey a message to the audience on the association norms of decency in scenes and dialogues in the film. Norms of decency is also contained in the Basic Competence Pancasila and Citizenship Education Class VII Junior High School namely: 3.4 Understanding the norms prevailing in a society, nation, and state. Implementation norms of decency is one character education subjects taught in Pancasila and Citizenship Education. Pancasila and Citizenship Education is one of the subjects that teach about good behavior that should be owned by learners.